"Hobson's choice" servicescape: consumer anxiety and enjoyment. Issue 7 (13th November 2017) - Bujisic, Milos; Bogicevic, Vanja; Yang, Wan; Cobanoglu, Cihan; Bilgihan, Anil
Abstract : Purpose: A Hobson's choice is a free choice in which only one option is offered. The aim of this study is to examine dimensions of "Hobson's choice" servicescape and their effect on affective responses and to understand how affective responses drive consumer decisions in "true choice" and "Hobson's choice" servicescapes. Design/methodology/approach: Two studies have been conducted. The first study used mixed methods approach (focus groups and online survey) to examine dimensions of "Hobson's choice" servicescape. The second study used a scenario-based experimental design to compare the effect of enjoyment and anxiety on consumer decisions in "true choice" and "Hobson's choice" servicescapes. Findings: Study 1 results indicate that hedonic and utilitarian servicescape attributes have a different effect on contrasting emotional responses. This study reveals a positive relationship between consumer enjoyment and hedonic stimuli in Hobson's choice servicescape. Furthermore, inadequate utilitarian servicescape dimensions cause consumer anxiety. Study 2 results indicate that enjoyment plays a more important role in consumer decision-making in true choice settings, whereas anxiety is more important in Hobson's choice settings. Research limitations/implications: Hobson's choice settings should focus on servicescape features that reduce anxiety and thus lead to affirmative consumer decisions. On the other hand, true choice settings should try to improve consumer enjoyment to create affirmative consumer decisions. Originality/value: This is the first study to examine and compare drivers of consumer's emotions and their effect on consumer decisions in Hobson's choice and true choice servicescapes.